THE ROLE OF AGRICULTURAL EXTENSIONERS IN THE DYNAMICS OF FARMER GROUP IN TANJUNG MEDAN SUB DISTRICT, ROKAN HILIR DISTRICT - Addindi, Bendri; Arifudin; Cepriadi (Jurnal Penyuluhan Pertanian, 2023)
The importance of the role of agricultural extension workers is carried out to bring up human resources in Tanjung Medan District so that they are able and willing to move dynamically to manage and develop farming activities in order to create prosperity. The large number of passive farmer groups is a problem in today's agricultural institutions. Therefore, quality improvement in agricultural activities will be supported and created if farmer groups and extension workers work together to achieve common goals. This research was conducted to determine the level of the instructor's role, the level of group dynamics and the influence of the instructor's role on group dynamics. This study used a survey method with 114 farmers as respondents who were selected by cluster sampling. Data were analyzed using a Likert scale and SEM test using Amos 24. Agricultural extension workers had carried out their role very well because they were in the very high category, namely the role of extension workers as facilitators, innovators, motivators, dynamists, educators, and consultants. The dynamics of farmer groups are classified as very dynamic because they are in a very high category, namely group objectives, group structure, group functions, group coaching and development, group cohesiveness, group atmosphere and group effectiveness. Then the role of agricultural extension agents has a significant effect on the dynamics of farmer groups, which means that the increasing role of agricultural extension agents will increase the dynamics of farmer groups in Tanjung Medan Sub District.